The influence of green accounting, intellectual capital and firm size on firm value in the sri kehati index - Muhammad Ilham; Khanti Listya; Anggiat Situngkir; Muhammad Asrin Jazuli (International Journal of Applied Finance and Business Studies, 2025)
This study examines the influence of Green Accounting, Intellectual Capital, and Firm Size on firm value among companies listed in the Sustainable and Responsible Investment (SRI)-KEHATI Index during 2020–2024. Using a quantitative archival approach, data from 10 purposively selected firms (50 firm-year observations) were analyzed through multiple linear regression with IBM SPSS 27. Based on Legitimacy Theory, firms disclose environmental information to maintain social approval and investor trust, while the Resource-Based Theory views intellectual capability and firm size as strategic resources that can enhance value when managed efficiently. The results show that Green Accounting has an insignificant effect on firm value (Sig. = 0.725), whereas Intellectual Capital (Sig. = 0.001; β = –0.048) and Firm Size (Sig. = 0.001; β = –0.047) have significant but negative effects. The simultaneous test (F = 5.690; Sig. = 0.002) confirms that all variables collectively influence firm value. This study contributes to the literature by demonstrating that sustainability practices and intangible resources do not automatically enhance firm value unless supported by operational efficiency, thereby refining the application of Legitimacy and Resource-Based Theories in the context of emerging sustainable markets.